Teenagers’ Public Library Needs are Difficult to Determine - Martin, Jason (Evidence Based Library and Information Practice, 2012)
Abstract Objective – To discover the attitudes of twelve to fifteen year-olds toward the public library. Design – Mixed methodology consisting of a survey and focus groups. Setting – An Eastern Canadian regional municipality. Subjects – Twelve to fifteen year-old middle school students. Methods – Using a disproportionate stratified sample and multistage clustering, the author mailed 900 surveys to middle school students; 249 surveys were completed and usable. Those students who completed the survey and who also indicated they would be willing to participate in a focus group were randomly selected to participate in nine focus groups with between 7 to 12 students in each group. Main Results – Discrepancies exist between the teens’ level of satisfaction with the library indicated on the survey (high) and expressed in the focus groups (low). Teens seldom use the public library due to: their non-existent relationship with library staff, although teens who were “active readers” used the library more; lack of appealing programs and program promotion; no teen-focused website; poor teen facilities within the library; and an overall failure of the public libraries to include teenagers. Conclusion – Public libraries need to be more responsive to teen needs to attract teens to use the library. To uncover these needs, libraries should use mixed methods of discovery.